SISTEM SELEKSI PENERIMAAN CALON KARYAWAN DENGAN MENGGUNAKAN METODE WEIGHTED PRODUCT (WP) - Donny Awardi; Nurjaya (CV. Multi Kreasi Media, 2022)
Employee selection is the process of finding and withdrawing job vacancies that have the potential to fill jobs, qualified workforce is very influential on company performance. (Ismail, Nurjaya, 2016). The employee selection system at PT. Currently, ZENSHO Indonesia is carried out conventionally, where the management determines the work without a clear selection process, giving the impression that the process is subjective. And there is no method used to determine the amount of value seen. In this study using the Weighted Product (WP) method, the advantages of the Weighted Product (WP) method are that there are Cost and Benefit variables, which are useful for determining criteria that affect decisions, and it is easier to reach this goal so that the selection process for determining work choices becomes more objective. , So that the process of calculating the quantities seen has a standard method. Based on the tests that have been carried out by building a permanent employee recruitment selection system at PT. ZENSHO Indonesia, the recruitment selection process becomes more objective. By applying the Weighted Product (WP) method to the recruitment selection process, the calculation process has definite parameters and criteria so that the process has a fixed standard method.